Antimicrobial activities of Allium staticiforme and Allium subhirsutum - Alican Bahadir Semerci; Dilek İnceçayır; Vusale Mammadova; Ayşegül Hoş; Kenan Tunç (Bangladesh Pharmacological Society, 2020)
The antibacterial and antifungal activities of the bulb and flower of Allium staticiforme and Allium subhirsutum were investigated. In addition, DPPH radical scavenging activity and total phenolic contents were determined. The results show that methanolic extracts of A. staticiforme and A. subhirsutum had antifungal activities against Candida albicans, together with a less activity level against Escherichia coli, Staphylococcus epidermidis, S. aureus, Enterecoccus faecalis, Salmonella typhimurium and Pseudomanas aeruginosa. The total phenolic contents of A. staticiforme leaf and bulb were determined as 17 and 2.4 mg of GAE/100 g, respectively. The IC50 of methanolic extracts of A. staticiforme and A. subhirsutum were also determined. In conclusion, both A. staticiforme and A. subhirsutum have antifungal activities with weak antibacterial activities. These plants have DPPH radical scavenging activities.